Le souci est, c'est que cette modification se fait à l'insu de l'utilisateur - Frédéric Sabio (Corela)
In French, specificational utterances containing an under-specified noun are likely to take a non-prototypical form in which the verb être [be] is realized twice: le problème est c’est que… [lit. the problem is it is that…]. Corpora indicate that although infrequent, such utterances are sufficiently well attested - especially with certain nouns such as preuve, fait, problème [proof, fact, issue] - to allow us to consider them as fully grammatical constructions rather than mere disfluencies. In terms of syntactic structure, we suggest describing them as constructions that amalgamate two distinct values of the verb être [be]: firstly, the value of a copula which licenses some temporal and apectual variation (est, était, étant [is, was, being]); secondly, the invariable form c’est [it is] which is described as a kind of auxiliary verb one would find in clefts or pseudo-clefts constructions.